Perancangan Sistem Informasi Penggajian Karyawan Dengan Metode Extreme Programming Pada Dom Social Hub - Ardyaksa, Aries; Fikri Romadhon, Muhammad; Ikhwanudin , Muhammad; Saprudin (CV. Shofanah Media Berkah, 2024)
Payroll information systems are a crucial aspect of human resource management to ensure efficiency and precision in the payroll procedure. This study intends to create a payroll data system by utilizing the Extreme Programming (XP) method at DOM Social Hub. The XP method was chosen for its flexibility in handling changing requirements and its ability to iteratively produce high-quality systems. The system development involved several stages, including data collection through documentation, literature reviews, interviews, and observation, as well as the implementation of XP principles such uch as short releases, test-driven development, and continuous integration. The system is designed to automate manual processes such as payroll computations, attendance monitoring, employee data administration, and report creation , thus reducing calculation errors and improving operational efficiency. Testing results indicate that the developed system successfully meets user needs, enhances accuracy, and provides a better user interface experience. With these outcomes, the system is expected to serve as an innovative solution supporting the digitalization of human resource management in the modern era.